Efficiency and productivity analysis of universal service obligation: a case of 29 designated operators in the European countries - Ralević, Predrag; Dobrodolac, Momčilo; Švadlenka, Libor; Šarac, Dragana; Đurić, Dejan (Technological and Economic Development of Economy, 2020)
The main aim of this paper is to perform efficiency and productivity analysis of Universal Service Obligation (USO) based on the Malmquist Productivity Indices (MPI) analysis. The study focuses on 29 Designated Operators (DOs) and two isolated periods, the years 2003 and 2017. There is a clear trend of workforce reduction (12%). Considering the postal services, the data confirm a general trend that the letter-post is in decline (30%) and the parcels are on the rise (52%). Considering the financial results, both costs and revenues are increased; however, there is a higher increase of revenue (33.13%) compared to the cost (32.61%). Further, the results of implemented methodology are twofold. Firstly, a progress is determined at the average level of all observed DOs according to the efficiency and productivity indicators. Among other, the results indicate the increase of productivity for both input MPI (3.5%) and output MPI (8%). However, there are significant variations of efficiency and productivity at the individual level. Secondly, the aim of research was also to examine the sources of productivity changes by considering postal market liberalization, ownership, marketing services and e-commerce. Our findings show that the last three specified variables contribute to the explanation of productivity change.First published online 28 February 2020